Entity Extraction and Annotation for Job Title and Job Descriptions Using Bert-Based Model - Fitri Ana Wati, Seftin; Fitri, Anindo Saka; Putra, Herlambang Haryo; Widodo, Suryo; Aziiza, Arizia Aulia (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2025)
This research paper investigates Named Entity Recognition (NER) within Indonesia’s job vacancy domain, employing state-of-the-art Bert-based models. The study presents a detailed data collection and preprocessing methodology, followed by the Bert-based model’s fine-tuning for enhanced NER. The dataset comprises 48,673 job vacancies collected from the JobStreet website in July 2023, specifically focusing on multi-entity recognition, including job titles and job descriptions. An original annotation algorithm was developed using Python and Laravel for precise entity recognition. In addition, this paper provides an extensive literature review of NER and Bert-based models and discusses their relevance in the context of the Indonesian job market. The outcomes highlight the efficacy of our BERT-based model, attaining an average accuracy of 78.5%, a precision of 79.7%, a recall of 81.1%, and an F1 score of 80.8% in the Named Entity Recognition (NER) task. The study concludes by discussing the implications, limitations, and future directions, underscoring the model’s potential applicability in streamlining job matching and recruitment processes in Indonesia and beyond. This research contributes to the field by providing a robust framework for NER in job vacancies, highlighting the potential for improved job matching, and proposing enhancements for future model development and application in other languages and regions.